The mental health crisis during the COVID-19 pandemic in older adults and the role of physical distancing interventions and social protection measures in 26 European countries - Mendez-Lopez, Ana; Stuckler, David; McKee, Martin; Semenza, Jan C.; Lazarus, Jeffrey V. (SSM - population health, 2022)
BACKGROUND: The COVID-19 pandemic and associated policy responses, such as physical distancing interventions, pose risks to mental health that could be mitigated by social support systems. We examine associations between changes in mental health in the population aged 50 years and older in Europe and stringency of pandemic responses and social protection. - METHODS: We analysed data from the Survey of Health, Ageing and Retirement in Europe: n = 50,278 individuals aged 50 years and older in 26 European countries between June and August 2020. Linear multivariable regression models were used to evaluate potential risk factors for deterioration in self-reported mental health and investigate whether social protection systems mitigate it. - RESULTS: Across the European Union, 28.1% (95% CI:27.1-29.2) of participants reported worsening mental health since the beginning of the pandemic, ranging from 16.1% in Slovakia to 54.8% in Portugal. Factors associated with increased risk of deterioration included: being female (12.7 percentage points (ppt), 95%CI:9.2-16.2); experiencing unmet healthcare needs during the pandemic (14.6 ppt, 95%CI:11.2-18.1); job loss during the pandemic (6.2 ppt, 95%CI:1.1-11.8); and financial hardship (5.1 ppt, 95%CI:2.9-7.2). Greater stringency of physical distancing measures in countries was associated with worsening mental health (0.2 ppt per each one point increase on a stringency index, 95% CI:0.09-0.4); however, country-level pre-pandemic expenditures on various social protection packages was associated with decreased probability of worsening mental health (-1.3 ppt, 95%CI: 0.3 to -2.3 per €1,000 increase in health care expenditures per capita and, among the unemployed, -3.8 ppt, 95%CI: 1.6 to -2.4 per €100 increase in unemployment expenditure per capita). - CONCLUSIONS: The COVID-19 pandemic has been associated with substantial mental health deterioration exhibiting social inequalities. Adverse mental health has been exacerbated by policy responses to the pandemic regulating physical distancing, but social protection expenditure might have helped mitigate the impact. Strengthening social protection systems might render the mental health of the population more resilient to the consequences of crises such as the COVID-19 pandemic.